Studying the alkylbenzenes sulfonation process using the mathematical model considering the mass transfer - Dolganova I. O. Irena Olegovna; Dolganov I. M. Igor Mikhailovich; Ivashkina E. N. Elena Nikolaevna; Zykova А. А. Anastasiya Aleksandrovna; Sladkov D. Yu. Denis Yurjevich (2024, 2024)
Title screen